If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 3a + 6 Reorder the terms: 18 = 6 + 3a Solving 18 = 6 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 18 + -3a = 6 + 3a + -3a Combine like terms: 3a + -3a = 0 18 + -3a = 6 + 0 18 + -3a = 6 Add '-18' to each side of the equation. 18 + -18 + -3a = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -3a = 6 + -18 -3a = 6 + -18 Combine like terms: 6 + -18 = -12 -3a = -12 Divide each side by '-3'. a = 4 Simplifying a = 4
| (7x+7)(x-5)= | | 4(r+3)=r | | x^2-144y^2=0 | | 65=2-5 | | 65=2n-5 | | 8a*6a= | | 2x=368-4 | | 214=1/3+n | | 3n+2=2n+1 | | 2j-5=8j | | 6+n=9 | | 2x+9=-15-2x | | 8[y+12]=100 | | 7.6x+4.2=-4.4x-19.8 | | 11x-1x-3x= | | 6x-64=2x-8 | | 2+-1x=5x+20 | | 27x^3+a^3=0 | | X^2-2xy-3y^2+2x-y+3=0 | | 30.8-6.4*x-4*y=0 | | -1x-9=8 | | 5(h-4)=5 | | 12/23=34/x | | 3m+2n= | | 1uponx-1-1uponx=1uponx+3-1uponx+4 | | 1uponx-1+2uponx-2=3uponx-3 | | 3-3-7-5=24 | | -10x+2y=0 | | 5(4y-3)=60 | | 5(4y+3)=60 | | 10x+1=3x+9 | | 2(d+6)=3(d-1) |